2021
DOI: 10.3390/ma14092134
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Modification of Agro-Industrial Waste-Based Bioadsorbents for Enhanced Removal of Zn(II) Ions from Aqueous Solutions

Abstract: Contamination of water by heavy metals is a major environmental concern due to the potential ecological impact on human health and aquatic ecosystems. In this work, we studied the chemical modification of various fruit peels such as banana (BP), granadilla (GP), and orange ones (OP) in order to obtain novel bio-adsorbents to improve the removal of Zn(II) ions from 50 mg·L−1 synthetic aqueous solutions. For this purpose, sodium hydroxide and calcium acetate were employed to modify the fruit peels. The moisture,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(8 citation statements)
references
References 84 publications
1
7
0
Order By: Relevance
“…To verify the suitability of the magnetite modified composite as adsorbents, a comparison with reports on other similar adsorbents in the literature was performed. Although direct comparison of the maximum adsorption capacity qm of studied lignocellulosic biomass-based adsorbents with literature is difficult, owing to the different experimental conditions, the maximum adsorption capacity obtained is in line with other reports on either same biomass sorbents (different analyte) [43] or adsorbents for Zn(II) obtained from various biomass such as Lagenaria vulgaris shell [44], modified orange peel [45] or [46] or magnetic water hyacinth [47]. Considering these findings and the cost-effective source of the obtained adsorbents, the laurel, canelo and eucalyptus biomass is considered a promising alternative to obtain highly effective adsorbents for water treatment.…”
Section: Adsorption Isothermssupporting
confidence: 85%
“…To verify the suitability of the magnetite modified composite as adsorbents, a comparison with reports on other similar adsorbents in the literature was performed. Although direct comparison of the maximum adsorption capacity qm of studied lignocellulosic biomass-based adsorbents with literature is difficult, owing to the different experimental conditions, the maximum adsorption capacity obtained is in line with other reports on either same biomass sorbents (different analyte) [43] or adsorbents for Zn(II) obtained from various biomass such as Lagenaria vulgaris shell [44], modified orange peel [45] or [46] or magnetic water hyacinth [47]. Considering these findings and the cost-effective source of the obtained adsorbents, the laurel, canelo and eucalyptus biomass is considered a promising alternative to obtain highly effective adsorbents for water treatment.…”
Section: Adsorption Isothermssupporting
confidence: 85%
“…There are numerous methods to remove phosphate from water, including chemical precipitation, biological treatment, physical process, coagulation, and adsorption [ 12 , 13 , 14 , 15 ]. Nevertheless, most of them, with the exception of adsorption, show drawbacks due to the high sludge production, the complexity of the process, and high operational costs compared with adsorption methods [ 16 , 17 ]. Adsorption has received immense interest due to its high removal efficiency, simple operation, better cost effectiveness, less or no sludge production, and invulnerability to coexisting pollutants [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In developing countries such as Ecuador, around 0.551 km 3 /year is extracted for the industrial sector, but data on industrial wastewater generated are not reported. The toxicity of the contaminants found in industrial wastewater, combined with the inadequate disposal, negatively affects ecosystems (reduction of species and changes in their composition, some of them are not biodegradable and get into the food chain and accumulate in the living organisms), and public health (e.g., skin diseases, anemia, low blood platelets, headaches, risk of cancer, diabetes, cardiovascular failure, damage to the skeletal, nervous, and immune systems, changes in cellular activities, such as neuronal activity, and gene expression) (Castro et al, 2021; Chowdhary et al, 2019; J. Kumar et al, 2011; Zhang et al, 2020). The contaminants found in industrial wastewater include heavy metals, dyes, oils, and emerging contaminants, among others.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, zinc is also an essential trace element for humans and aquatic organisms, nevertheless, in higher concentrations could be toxic to both (Kara et al, 2017). Aquatic organisms are more sensitive (criteria of zinc to protect freshwater aquatic organisms = 120 µg/L) than humans (criteria for human health = 7400–26,000 µg/L) (Castro et al, 2021; Li, Liu, et al, 2019). Therefore, the removal of zinc from wastewater is necessary to avoid the problems associated with its toxicity.…”
Section: Introductionmentioning
confidence: 99%